Thermal study of ZrO2 nanoparticles: Effect of heating and cooling cycles on solid-solid transition - Gaglieri, Caroline [UNESP]; Alarcon, Rafael T. [UNESP]; de Godoi Machado, Rafael [UNESP]; Padovini, David S.S. [UNESP]; Pontes, Fenelon M.L. [UNESP]; Caires, Flávio J. [UNESP] (Elsevier, 2017)
This study investigates the influence of particle size on the solid-solid transition in zirconium (ZrO2) nanoparticles. The Simultaneous Thermogravimetry/Derivate Thermogravimetric-Differential Thermal Analysis (TG/DTG-DTA) was used to evince the phase transitions processes as well as the quantity of volatile compounds and the residual organic matter formed during the synthesis of nanoparticles. Field Emission Scanning Electron Microscopy (FE-SEM) and Transmission Electron Microscopy (TEM) were used to prove the increase and agglomeration;1;of particle size after each thermal cycle.
Keywords: Solid-solid transition; Thermal analysis; ZrO2 nanoparticles